2022
DOI: 10.3389/fvets.2022.1058110
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Campylobacter hepaticus specific antibodies among commercial free-range layers in Australia

Abstract: Spotty liver disease (SLD) caused by Campylobacter hepaticus affects the health and productivity of layer hens and is a disease of concern in poultry. In this study, blood and cloacal swab samples were collected from 709 birds across 11 free-range layer farms from different regions of Australia. The prevalence of C. hepaticus specific antibodies and DNA was assessed using a C. hepaticus specific ELISA and PCR and its correlation with mortalities and changes in egg production was analyzed to better understand t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 23 publications
1
5
0
Order By: Relevance
“…It is evident that C. hepaticus may be present and circulating in a flock of hens well before an outbreak of SLD occurs and may be present in flocks that never show a disease outbreak. This has also been observed by Phung et al (2020) and Muralidharan et al (2022). This was shown first by detection of positive C. hepaticus antibody serology, some weeks before cloacal swabs began to expose its presence, within the small 12 sample size employed in this study.…”
Section: Discussionsupporting
confidence: 83%
See 3 more Smart Citations
“…It is evident that C. hepaticus may be present and circulating in a flock of hens well before an outbreak of SLD occurs and may be present in flocks that never show a disease outbreak. This has also been observed by Phung et al (2020) and Muralidharan et al (2022). This was shown first by detection of positive C. hepaticus antibody serology, some weeks before cloacal swabs began to expose its presence, within the small 12 sample size employed in this study.…”
Section: Discussionsupporting
confidence: 83%
“…Two earlier surveys showed a prevalence of 45% and 43.5% respectively where houses had fully slatted floors ( Gao et al, 2023a ; Gao et al, 2023b ). A study by Muralidharan et al (2022) reported 6 out 12 flocks had experienced clinical SLD, but the individual house designs were not declared. The objective of the present study was to provide descriptive epidemiological information on the occurrence of SLD in Australian cage-free flocks where the house incorporated a scratch area.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Nevertheless, considering the extra resources and time required for performing the pre-absorption step in SLD-ELISA1, SLD-ELISA2 is a more convenient option, especially when working with large sample sizes as in the identification of the seroconverted birds in farms or in assessing the immune response of birds in large scale experimental infection studies. SLD-ELISA2 has been used to assay sera samples collected from more than 700 birds in commercial free-range farms to better understand the seroprevalence of anti- C. hepaticus antibodies in Australian free-range farms ( 42 ).…”
Section: Discussionmentioning
confidence: 99%